Obstructive sclerotic arteriopathy of superficial femoral thromboendarterectomy venous plastic reconstruction - Suiffet, Walter; Priario, Julio C; Varela, Nelson (Cirugía del Uruguay, 2020)
Presented at session 24th July 1963